Effectiveness of education intervention of tuberculosis treatment adherence in Khartoum State: A study protocol for a randomized control trial. - Khalda Mohamed Khamis; Hayati Kadir Shahar; Rosliza Abdul Manaf; Hamdan Mustafa Hamdan (PLoS ONE, 2022)
Background Treatment failure and disease relapse among tuberculosis (TB) patients are commonly caused by non-adherence. It can lead to prolonged infection, increased transmission, drug resistance, and loss of life. Even though the causative microorganism of TB has been identified for more than a century, the disease is still a substantial public health problem worldwide. This research aims to devise, implement, and assess an educational intervention to improve adherence to TB treatment. Methods and findings A randomised clinical trial involving 146 Sudanese TB patients will be conducted at the Abu Anga hospital in Khartoum. The participants will be randomly assigned to the intervention and control groups. A 2-hour session will be offered to the intervention group in a one-day TB educational intervention course. The same educational materials will also be provided to the control group after the randomised controlled trial (RCT). Data will be collected at baseline, one month, and four months after the intervention. The primary outcome of interest is TB treatment adherence, while secondary outcomes include quality of life score, tuberculosis knowledge, and health belief domains. Generalised estimating equations (GEE) in SPSS software version 25.0 will be utilised to evaluate the changes over time. Conclusions This trial will provide information that could be used in improving TB control strategies to achieve better results in the adherence of healthcare services to the norms of the National Program and patient adherence to the disease treatment and cure. Trial registration This study is registered at TCTR: (TCTR20210607006).